2020
DOI: 10.1080/19932820.2020.1741904
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating of altered hydration status on effectiveness of body composition analysis using bioelectric impedance analysis

Abstract: Body composition analysis may provide valuable information about the assessment of balance between fluid, fat, and fat-free mass. The present study assessed whether the regular increase in water consumption has any significant effects on measurements of body composition using BIA. A total of 140 subjects participated in this study. Body composition analyses of the subjects were performed for five times using foot to foot BIA; first at baseline and four times, after 15 minutes of each 500 mL water intakes. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 26 publications
2
24
0
1
Order By: Relevance
“…There are several other findings in the literature that are compatible with this interpretation. One study conducted among healthy young women with TWI below 2L/d demonstrated that a sustained increase in total drinking fluids of +0.5 L/day for 6 weeks might result in slow recovery of TBW from an initial <3% TWI deficit [ 50 ]. Additionally, one study confirmed the increases in TBW after four periods of acute water consumption of 500 mL compared with the baseline among males and females [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several other findings in the literature that are compatible with this interpretation. One study conducted among healthy young women with TWI below 2L/d demonstrated that a sustained increase in total drinking fluids of +0.5 L/day for 6 weeks might result in slow recovery of TBW from an initial <3% TWI deficit [ 50 ]. Additionally, one study confirmed the increases in TBW after four periods of acute water consumption of 500 mL compared with the baseline among males and females [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…For ethical reasons, children were not asked to fast before BIA measurement. If children consumed large volumes of water shortly before the BIA measurement, percent body fat may have been overestimated 40 . Finally, while high and low LPA variables were created, there was too little time spent in high LPA to conduct analyses with this variable.…”
Section: Discussionmentioning
confidence: 99%
“…The muscle mass and body cell mass are important for individuals practicing sports [ 38 ], as well as malnourished [ 39 ], sarcopenia [ 40 ], elderly [ 41 ], and critically ill patients [ 42 ]. At the same time, extracellular water and intracellular water are especially important for individuals experiencing body fluid disturbances, including dehydrated [ 43 ], kidney disease [ 44 ], and cardiovascular diseases patients [ 45 ].…”
Section: Discussionmentioning
confidence: 99%